Christabel Pankhurst : fundamentalism and feminism in coalition - Larsen, Timothy, 1967- (Studies in modern British religious history., 2002)
Christabel Pankhurst was arguably the most influential member of her famous family in the struggle to win the vote for women in the years before the First World War. Paradoxically, she has also been the most neglected subsequently by historians. Part of the reason for this may be that, in the years after women's suffrage had been achieved in 1918, she turned her energies to Christian fundamentalism and carved out a new career as a writer of best-selling evangelical books and as a high-profile speaker on the fundamentalist preaching circuit, particularly in the United States.